Emotional dysregulation in women with endometriosis with cyclical and non-cyclical chronic pelvic pain - Dulce Carolina Rodríguez-Lozano; María del Pilar Meza-Rodríguez; Olivier Paul Cruz-Orozco; Brenda Sánchez-Ramírez; Andrea Olguin-Ortega; José Roberto Silvestri-Tomassoni; Guillermo Corona-Barsse; Luis Fernando Escobar-Ponce; Juan Mario Solis-Paredes; Benjamín Dominguez-Trejo; Ignacio Camacho-Arroyo (BMC, 2022)
Abstract Background Endometriosis is a pathophysiological condition characterized by glands and stroma outside the uterus in regions such as the bladder, ureter, fallopian tubes, peritoneum, ovaries, and even in extra pelvic sites. One of the main clinical problems of endometriosis is chronic pelvic pain (CPP), which considerably affects the patients' quality of life. Patients with endometriosis may, cyclically or non-cyclically (80% of cases) experience CPP. High levels of anxiety and depression have been described in patients with endometriosis related to CPP; however, this has not been evaluated in endometriosis women with different types of CPP. Therefore, the research question of this study was whether there is a difference in the emotional dysregulation due to the type of pain experienced by women with endometriosis? Methods This work was performed in the National Institute of Perinatology (INPer) in Mexico City from January 2019 to March 2020 and aimed to determine if there are differences in emotional dysregulation in patients with cyclical and non-cyclical CPP. 49 women from 18 to 52 years-old diagnosed with endometriosis presenting cyclical and non-cyclical CPP answered several batteries made up of Mini-Mental State Examination, Visual Analog Scale, Beck's Depression Inventory, State Trait-Anxiety Inventory, and Generalized Anxiety Inventory. Mann-Whitney U and Student's t-test for independent samples to compare the difference between groups was used. Relative risk estimation was performed to determine the association between non-cyclical and cyclical CPP with probability of presenting emotional dysregulation. Results We observed that patients with non-cyclical CPP exhibited higher levels of depression and anxiety (trait-state and generalized anxiety) than patients with cyclical pain, p < 0.05 was considered significant. No differences were observed in pain intensity, but there was a higher probability of developing emotional dysregulation (anxiety or depression) in patients with non-cyclical CPP. No differences were observed in cognitive impairment. Conclusions Our data suggest that patients with non-cyclical (persistent) CPP present a higher emotional dysregulation than those with cyclical pain.